Wejście smoka - Poprzęcka, Maria (Artium Quaestiones, 2019)
The paper is a reminiscence of my first meeting with the colleagues from the Institute of Art History of Adam Mickiewicz University, which took place at an annual conference of the Association of Art Historians in 1974, titled “Reflection on Art.” Choosing an unusual title, I wanted to convey the impetus with which a group of young art historians from Poznań entered the decent and somewhat stagnant stage of Polish art history. The critique they presented was directed against Polish academic institutions, the problematic of the conference, the empty rituals of academic life, etc. Even though I did not accept all their objections, the heated debate suddenly turned out for me to be a liberating factor, stimulating continuous critical thinking which is an antidote for spiritual and intellectual captivity.